Bottom-Up Kinetic Chain in Drop Landing among University Athletes with Normal Dynamic Knee Valgus - Nazatul Izzati Jamaludin (International Journal of Environmental Research and Public Health, 2020)
The study investigated the influence of ankle strength and its range of motion (ROM) on knee kinematics during drop landing. Fifteen male and fifteen female university athletes with a normal range of dynamic knee valgus (DKV) (knee frontal plane projection angle: men = 3° to 8°, females = 7° to 13°) were recruited. They performed drop landing at height 30 cm and 45 cm with three-dimensional motion capture and analysis. Knee angles were compared at specific landing phases. Isokinetic ankle strength was tested at 60°/s angular velocity while the weight-bearing lunge test was conducted to evaluate ankle ROM. For males, strength for both plantarflexors and dorsiflexors were associated with knee kinematics at both heights (30 cm: r = −0.50, p = 0.03; 45 cm: r = −0.45, p = 0.05) during maximum vertical ground reaction force (MVGRF) phase. For females, ankle invertor strength and knee kinematics were associated at both 30cm (r = 0.53; p = 0.02,) and 45 cm landing heights (r = 0.49, p = 0.03), while plantarflexor strength and knee kinematics showed a significant association during initial contact (r = 0.70, p < 0.01) and MVGRF (r = 0.55, p = 0.02) phases at height 30 cm only. Male and female athletes with normal range of DKV showed a significant relationship between ankle strength and knee kinematics at specific landing phases. These relationships varied with increased landing height.